Critical Thinking And 21st-Century Skills: Evaluating The Effectiveness Of Problem-Based Learning Models In Multicultural Classrooms - Suyono; Prijo Harsono; Erwin Sutantyo; Putranto, Wahyu Ari; Juwarlan (PT Inovasi Pratama Internasional, 2025)
This qualitative study examines the effectiveness of Problem-Based Learning (PBL) models in developing critical thinking and 21st-century skills among middle school students in multicultural classroom environments. Through an interpretive qualitative approach employing in-depth interviews, classroom observations, and focus group discussions, this research explores how PBL methodologies foster active learning and enhance students' analytical capabilities across diverse cultural backgrounds. The study involved 24 middle school teachers and 72 students from three multicultural schools in Indonesia, implementing a purposive sampling strategy. Data analysis utilized Braun and Clarke's reflexive thematic analysis framework to identify patterns and themes related to critical thinking development and cross-cultural learning experiences. Findings reveal that PBL significantly enhances students' critical thinking abilities, promotes collaborative problem-solving skills, and facilitates meaningful cross-cultural interactions. The research demonstrates that multicultural PBL environments create authentic learning opportunities where students develop both cognitive and social competencies essential for 21st-century success. However, implementation challenges include teacher preparation requirements, resource limitations, and the need for culturally responsive instructional materials. The study concludes that well-structured PBL approaches in multicultural settings effectively prepare middle school students for complex problem-solving while fostering intercultural understanding and communication skills. These findings contribute to educational scholarship by providing evidence-based insights into the integration of active learning methodologies with multicultural education frameworks